Government intervention and eradication of the anemia in pregnant adolescents, Peru - Vicente-Perez, Luisa J (2023)
Objective. Describe the importance of the Government Intervention by the enactments of laws to favor the eradication of anemia in Peru. Likewise identify the relationship between the factors selected and the Prevalence of Anemia on pregnant adolescents in Peru. Methods. A quantitative, explanatory, and cross-sectional study was carried out, A review of the legal framework in the Public Policies and the commitments assumed by the different entities of the Peruvian state in their fight to eradicate the anemia on pregnant adolescents in Peru. For the representation of the sample, integrates and synthesized of geographic and descriptive information from various sources corresponding to the regions of Peru in the year 2012 to 2018 the ArcGIS program were used. For the analysis of statistical data, the SPSS program were used. Likewise, logistic regression with 95% confidence interval were applied, which is considered highly feasible; The level of significance established was p value (< 0.01) less than 0.05. Results. The study included pregnant adolescents. The negative correlation: Iron supplement (IS) with -0,648, growth and development control (GDC) with -0,739, treated water (TW) with -0,461, basic sanitization (BS) with -0,478, total budget in millions Peruvian currency (TBPC) with -0,691, monitoring total budget in millions peruvian currency (MTBPC) with -0,578. Positive correlation: Breastfeeding (BR) with 0,641, teenage mother (TM) with 0.757. Conclusion. It is concluded that the intervention of the Peruvian Government as a central axis for the eradication of anemia on pregnant adolescents in Peru is of vital importance since it facilitates communication as well as the exchange of information, allowing the articulation of the different actors involved with the eradication of anemia contributing to better and more efficient teamwork in the search for a single common goal.